Regional tourism during the COVID-19 pandemic: Losses, missed opportunities and new developments for the tourism industry - Gierczak-Korzeniowska, Beata; Szpara, Krzysztof; Stopa, Mateusz (Turyzm/Tourism, 2021)
As a result of the spread of the COVID-19 pandemic, tourism, as one of the branches of many national economies, has suffered heavy losses both nationally and regionally. The pandemic as a global phenomenon is bound to change tourism, at least for some time to come. Therefore, questions arise about the nature of these changes and how deep they will be. The aim of the article is to show that for Podkarpackie Province in Poland, the COVID-19 pandemic, apart from the obvious negative consequences for the tourism industry, has also brought new development opportunities. The analyses presented here are based on a survey conducted among 948 adult respondents in 10 different locations within three districts between 15 and 30 August 2020. The analysis showed that during the pandemic, nature-related travel and active tourism, as well as trips aimed at health recovery were in high demand. Ensuring health and safety on holidays became a priority. Therefore, a concentration of tourism was observed in selected domestic destinations, usually in areas not associated with tourism (e.g. rural areas). In the future, this may create opportunities for a revival of local tourism. In contrast, the tourism industry suffered its greatest losses in cities; business and event tourism lost out, and there was a significant drop in revenue from both domestic and foreign tourists. These results indicate the negative effects of the pandemic, but also show new development opportunities. No one knows how long COVID-19 will continue, so the conclusions may be useful both for entrepreneurs preparing their tourist offers in the coming years, and institutions responsible for regional tourism policy.